Determinan Perilaku Seksual Berisiko pada Remaja - Chaerani, Erni; Yasin, Dudella Desnani Firman; Abilowo, Ashar; Windiarti, Sri Endang; Widiyati, Sri (Journal of Telenursing (JOTING), 2025)
This research aims to determine the determinants of sexual risk behavior in adolescents. The research method used a cross sectional design, with a sample of teenagers aged 15 to 21 years totaling 348 respondents. The research results show that there is a significant relationship between the role of peers, the role of parents and exposure to social media with sexual risk behavior in adolescents. The results of the analysis obtained the highest OR value for the peer role variable (OR=3.176), peers played a role 3.176 times in having sexual risk behavior. In conclusion, the effective role of parents and teachers both at home and at school is expected to prevent sexual risk behavior in adolescents. Keywords: Determinants, Behavior, Adolescent,s Sexual